Грушевое яблочко: [рассказ] / Л. Воронкова ; художник Н. Трепенок - Воронкова Любовь Федоровна (Малыш, 1986)
Экземпляры: ф.17 (20210513) / Инвентарный номер: бр / Цена: 03.00 / Авт.знак: В75 / ГРНТИ: 17.82.93 / ББК: 84(2 Рос=Рус)6